Luaran Penggunaan Analgesik Opiat pada Pasien Kanker - Salma Fajar Puspita; Zullies Ikawati, Apt.; Retno Muliawati (Faculty of Pharmacy, Universitas Gadjah Mada)
Cancer pain might reduce the quality of life of cancer patients. Opioids are the drug of choice in cancer pain management. Fentanyl and other opioids are often prescribed. This study was aimed to compare the pain intensity reduction and quality of life of patients with cancer pain using transdermal fentanyl and other opioids. This prospective cohort study Oinvolved cancer outpatients with pain at the Tulip International Cancer Center of RSUP Dr. Sardjito, Yogyakarta fulfilling inclusion and exclusion criteria. Follow-up was carried out 2 weeks after recruitment. Pain intensity and quality of life were obtained through interview process using Numerical Rating Scale (NRS) and EORTC QLQ-C30 questionnaire. Patient demographic and disease status were obtained from medical records. Clinical outcomes (reduction in pain intensity and achievement of pain targets) and quality of life in the transdermal fentanyl and oral opioid groups were presented descriptively because of the low research power. Total respondents involved were 111 patients, 13 (11.71%) patients used transdermal fentanyl and 98 (88.29%) patients used oral opiates. The effect of opioid on reduction of pain intensity, achievement of pain targets and quality of life cannot be justified even though descriptively transdermal fentanyl shows better outcomes than oral opioid. The reduction of pain intensity was influenced by age (p = 0,000) and global health status was influenced by the stage of the cancer (p = 0.045).